Meta-analysis of Immunochip data of four autoimmune diseases reveals novel single-disease and cross-phenotype associations - Ana Márquez; Martin Kerick; Alexandra Zhernakova; Javier Gutierrez-Achury; Wei-Min Chen; Suna Onengut-Gumuscu; Isidoro González-Álvaro; Luis Rodriguez-Rodriguez; Raquel Rios-Fernández; Miguel A. González-Gay; Coeliac Disease Immunochip Consortium; Rheumatoid Arthritis Consortium International for Immunochip (RACI); et al. (Genome Medicine, 2018)
Abstract Background In recent years, research has consistently proven the occurrence of genetic overlap across autoimmune diseases, which supports the existence of common pathogenic mechanisms in autoimmunity. The objective of this study was to further investigate this shared genetic component. Methods For this purpose, we performed a cross-disease meta-analysis of Immunochip data from 37,159 patients diagnosed with a seropositive autoimmune disease (11,489 celiac disease (CeD), 15,523 rheumatoid arthritis (RA), 3477 systemic sclerosis (SSc), and 6670 type 1 diabetes (T1D)) and 22,308 healthy controls of European origin using the R package ASSET. Results We identified 38 risk variants shared by at least two of the conditions analyzed, five of which represent new pleiotropic loci in autoimmunity. We also identified six novel genome-wide associations for the diseases studied. Cell-specific functional annotations and biological pathway enrichment analyses suggested that pleiotropic variants may act by deregulating gene expression in different subsets of T cells, especially Th17 and regulatory T cells. Finally, drug repositioning analysis evidenced several drugs that could represent promising candidates for CeD, RA, SSc, and T1D treatment. Conclusions In this study, we have been able to advance in the knowledge of the genetic overlap existing in autoimmunity, thus shedding light on common molecular mechanisms of disease and suggesting novel drug targets that could be explored for the treatment of the autoimmune diseases studied.